Alms and Vagabonds: Buddhist Temples and Popular Patronage in Medieval Japan - Kabanoff, Alexander M (Japanese religions, 1996)
Review of Goodwin, Janet R. Alms and Vagabonds: Buddhist Temples and Popular Patronage in Medieval Japan. Publisher: Honolulu : Univ of Hawaii Pr, 1994